Growth Requirement, Mass Production and Application of Trichoderma Harzianum as a Growth Enhancer of Oil Palm - Sebran, Noor Haida (2008)
Several species of the genus Trichoderma were reported to be effective biological control agents of plant diseases with Trichoderma harzianum being one of the most documented biological control agents of various plant pathogens. Previous studies have shown that T. harzianum (isolate FA 1132) has good properties as a biological control agent against basal stem rot (BSR) of oil palms, caused by the bracket fungus Ganoderma boninense. This study found that FA 1132 grew well in both the solid (MFOP) and liquid media (PDB, POME) tested. The best carbon and nitrogen source were D-fructose and L-asparagine, respectively. The optimal growth temperature was at the ambient temperature of 28±2°C, while the optimum pH level was between pH 2.7 to pH 6.0. This study also found that 3% sucrose concentration in PDB and MFOP, and 9% molasses or jaggery in POME, gave maximum mycelial yield of FA 1132. Shake flask cultures at 12 hours/day gave higher mycelial yield of FA 1132 compared to static flask cultures, while shake flask cultures at 24 hours/day were not significantly different from 12 hours/day over 14 days of experiment. For its application in the field, T. harzianum has to be produced on a large scale in a suitable carrier. This isolate has to self-proliferate in a cheap and easily available organic media and within a relatively short period of time. Preliminary studies showed that wastes from the oil palm industry, namely mesocarp fibres of oil palm (MFOP) were good and practical substrates. A potent inoculant of FA 1132 was successfully prepared via submerged fermentation with an agitation speed of 1000 rpm and 50% dissolved oxygen tension level for 96 hours. The mean conidial count by this method was 7.73 x 109 conidia/ml. This conidial suspension was turned into a solid inoculum for solid substrate fermentation, at 5 kg per 50 tonnes palm press fibre waste, which were piled into windrows of 50 m dimension. Liquid palm oil mill effluent (POME) was given as a nitrogenous supplement at 16 tonnes within the first 8 weeks. The presence of T. harzianum was monitored every 3 weeks over a 27-week period. Results showed that the trend towards an increased Trichoderma population started at week 6 and reached its peak of 4.07 x 108 conidia/g at week 15, when the product was ready for packaging. Conidial counts of the product at 8 weeks after bagging in 25 kg bags was 5.10 x 108 conidia/cfu/g, indicating a slight increase in population during storage. Thus, T. harzianum (FA 1132) was found to sustain well during mass production and the FA 1132 inoculant was able to generate a pilot scale production of 22mt of Trichoderma end product per run. When the formulated FA 1132 was applied onto newly planted field palms, Treatment 2 (which is treatment applied directly into the planting hole) gave a significantly better growth performance than palms applied with fertilizer and untreated control. Similarly, based on the summation of the growth response, T2 gave the best growth response to the treatment for every parameter. In conclusion, T. harzianum (FA 1132) produced good biological characteristics which were suitable to be used to upscale the propagule production of FA 1132 by submerged fermentation and mass produce it on a larger scale by solid substrate fermentation. Formulated FA 1132 was found to be a good growth enhancer of oil palms based on field trials.